2020
DOI: 10.1016/j.bbmt.2020.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Fludarabine/Busulfan Conditioning-Based Allogeneic Hematopoietic Cell Transplantation for Myelofibrosis: Role of Ruxolitinib in Improving Survival Outcomes

Abstract: Allogeneic hematopoietic cell transplantation (allo-HCT) is the only curative treatment modality for primary myelofibrosis (MF) and related myeloproliferative neoplasms. Older age at diagnosis and age-related comorbidities make most patients ineligible for allo-HCT, given concerns for nonrelapse mortality (NRM). Here we report the outcomes of 37 consecutive recipients of allo-HCT for MF performed at a single center between 2009 and 2018 with a standardized institutional protocol. Most patients received ruxolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…33 We could not demonstrate any effect of pre-transplant JAKi on survival. Recent studies [38][39][40][41][42] have reported encouraging survival outcomes in MF patients who prior to transplantation is associated with improved outcomes. 44,45 We did not find any effect of splenectomy or spleen size on survival outcomes or engraftment times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 We could not demonstrate any effect of pre-transplant JAKi on survival. Recent studies [38][39][40][41][42] have reported encouraging survival outcomes in MF patients who prior to transplantation is associated with improved outcomes. 44,45 We did not find any effect of splenectomy or spleen size on survival outcomes or engraftment times.…”
Section: Discussionmentioning
confidence: 99%
“…routinely received JAKi pre-transplant. One such report by Chhabra et al38 reported a 3-year OS of 81.1% and 3-year RFS of 78.4% in a cohort of 37 patients, and there were no primary graft failures. The authors postulated that the potential benefits of ruxolitinib in reducing GVHD, NRM, and relapse could be responsible for the improved survival.…”
mentioning
confidence: 96%
“…Please refer to a previous publication for additional information on the conditioning regimens used in these patients and the transplant outcomes. 18 As part of the protocol, patients with MPN with splenomegaly measuring greater than 22 cm were referred for splenic irradiation, with the final fraction completed 1 day before scheduled admission for conditioning.…”
Section: Methodsmentioning
confidence: 99%
“…Recently Chabra et al. published a small number of MF patients, mostly treated with ruxolitinb pre-transplant ( 71 ): after a median follow up of >3 years, two patients out of 37 had relapsed after HSCT (5.4%), but the study lacked a strong control group of untreated ruxolitinib patients. Indeed other recently published data in the ruxolitinib era ( 72 ), have shown no improvement in survival nor in the incidence of relapse for MF.…”
Section: Treatment Of Mf Relapse After Allogeneic Transplantmentioning
confidence: 99%